Goriller İçinde: One of the Earliest Examples of the Fantasy Genre in Turkish Literature - Elif Türker (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Halit Eyüp wrote four novels: Sevda-yı Nihan, Goriller İçinde, Nermin and Şadi. He was one of the writers of the Mutavassitin Group, advocating a more restrained approach to both the West and the East. Eyüp expressed his ideas across various genres, but Goriller İçinde stands out as particularly significant within his novelistic work. This novel draws upon Ahmet Mithat Efendi’s text “Bir Acibe-i Saydiye”, echoing Ahmet Mithat Efendi’s reflections on the theory of evolution. Set against the backdrop of the period’s Darwinism debates, the novel adopts a cynical perspective on the discussions surrounding human origins, employing conventions of fantastic literature. This study examines Goriller İçinde through the lens of Tzvetan Todorov’s theory of the fantastic. The analysis reveals that the novel aligns with Todorov’s criteria for the genre, particularly in its treatment of supernatural events, which are narrated by the protagonist Ahmet Nebil and diverge sharply from conventions of fairy tales, marking a defining feature of the fantastic novel. Correspondingly, the construction of reality in Goriller İçinde is deliberately maintained at a level that provides hesitation and ambivalence, which are emphasized by Todorov. The fact that Ahmet Nebil, an ordinary individual, serves as the narrator heightens the emotions of fear, horror, and curiosity within the story, which is another quality that Todorov identifies as central to the fantastic. Preserving this sense of curiosity and suspense is another key criterion of the fantastic, and in Goriller İçinde, this is achieved through Ahmet Nebil’s recurrent encounters with dangers as the story unfolds. The primary aim of this study is to demonstrate how these features are strategically constructed to critique, and even satirize, the Darwinist views prevalent during the period